ESG Disclosure in Mining Companies: The Moderating Role of Political Connections in the Influence of Public Ownership and Firm Size - Taufiqurrahman Taufiqurrahman; Fachrul A Siregar (Jurnal Multidisiplin Sahombu, 2026)
This study examines the effect of public ownership and firm size on ESG disclosure, with political connection as a moderating variable, in mining companies listed on the Indonesia Stock Exchange during the 2022-2025 period. Using a quantitative approach, data were collected from the annual reports and sustainability reports of 10 purposively selected mining companies observed over four years, producing 40 firm-year observations. Multiple linear regression was used to examine the direct effects of the independent variables on ESG disclosure, while Moderated Regression Analysis (MRA) was applied to test the moderating role of political connection. The results indicate that public ownership has a positive relationship with ESG disclosure, whereas firm size shows no significant effect on ESG disclosure. Political connection is found to strengthen the effect of public ownership on ESG disclosure, while its moderating effect on the relationship between firm size and ESG disclosure is comparatively weaker. These findings suggest that political connection can encourage mining companies, particularly those with substantial public ownership, to be more proactive in ESG disclosure. This study highlights the importance of political ties in improving transparency and sustainability reporting in the mining sector.